Seismic performance of RC columns under combined cyclic flexural and constant axial loadings - Aydemir, Cem; Aydemir, Muberra Eser; Arslan, Guray (ELSEVIER SCIENCE INC, 2023)
In this study, an experimental test procedure is conducted to investigate seismic performance of reinforced concrete columns under earthquake loading. Earthquake loading is simulated by combination of constant axial load and reversing cyclic load. The main variables of the experimental program are selected to be dimensionless axial load level and the ratio of shear span to effective column depth. Test results are compared with the current suggestions and approximations used for performance-based design and/or evaluation of reinforced concrete (RC) columns under seismic loads. It is observed that section curvature plays an important role to express failure damage limit state under cyclic loading as well as to sudden decrease in load carrying capacity. Besides, two new simple suggestions are made for performance-based design and/or evaluation process of RC columns. As a first step of this suggestions, a relation between damage limit states and curvature ductility ratios of RC columns is defined. This relation is validated with the experimental results of test columns through damage index model based on section curvature. The proposed damage limit states vary according to damage level definition and based on buckling parameter in terms of diameter, buckling length and yield strength of longitudinal reinforcement. The second suggestion is made to relate damage limit state to decrease in shear resistance of columns. To this purpose, a model to express concrete contribution to shear strength due to the proposed damage limits is used. With these two new proposed equations, it is both aimed to obtain a damage limit state in terms of curvature ductility ratio and to control ductile failure mode in a simple yet effective way.
Keywords: Earthquake engineering; Seismic design; Performance based design; RC columns; Curvature ductility; Concrete contribution to shear strength; Damage model; REINFORCED-CONCRETE COLUMNS; SHEAR-STRENGTH; CAPACITY; MODEL; Engineering